Inovação na justiça: análise do prêmio Innovare no contexto nacional e no Estado do Amazonas - Filizola, Kamila de Souza (Brasil, 2023)
Public organizations are increasingly looking for innovations that tolerate their main objective: to serve the public interest. This study seeks to descriptively understand the focus of innovative actions in justice in Brazil and in the State of Amazonas, and to make a comparison between innovative practices in Amazonas and in other states of the country. It analyzes the deferred entries from the years 2021 and 2022 of the Innovare award, which aims to demonstrate the actions and problems solved with them, by Justice Bodies, such as Public Ministry, Courts, Defender and other categories. The Methodology has a documental character as it researched the data on the Innovare Prize website, using a previously defined instrument for the analyses. It was concluded with the analysis of the quantitative data and with the statistical statistics in the tables that the tendency of the innovations is the service to the citizen and that the Amazon acts in a similar way to the rest of the country regarding the areas where innovation projects are carried out.